Exploring Naturmolnet’s qualities that promote well-being in the public place : pocket parks for a better urban life? - Paolini Madrid, Rebeca (SLU/Dept. of People and Society, 2022)
Green public places are in constant threat due to city development and densification. For the benefit of the urban dwellers and the environment, it is important to the development, accessibility, and quality design of public places. Pocket parks are an urban phenomenon, a type of small public place in between buildings, that represents a restorative escape from the roughness of everyday city life. This thesis explored and investigated how Naturmolnet, a pocket park in Malmö, contributes to the restoration and improvement of urban life. The methodology used in this project was an expert observation landscape analysis which was assisted by a protocol tool developed from an initial review of the scientific literature on both pocket parks and the Perceived Sensory Dimensions model (PSD). This protocol was used to evaluate the characteristics and qualities in Naturmolnet that fosters restoration and promotes well-being. With a 5-point Likert scale and a checklist, the eight PSDs and pocket parks characteristics were evaluated. The results of this study suggested that Naturmolnet included most of the pocket park characteristics and restorative elements from different PSD qualities. The PSDs Cultural, diverse, and social scored the highest (5 points). Sheltered and open scored in the middle (3 points). Natural, cohesive, and serene scored the lowest (1 point). Overall, the results indicated that even though Naturmolnet was not considered a natural and serene environment, it had other elements equally important like social and cultural that classify it as a restorative urban place that promotes well-being. In conclusion, Naturmolnet is a high-quality pocket park that functions as a dynamic environment, with a balance between natural, cultural, and social aspects. Naturmolnet is a community-driven place in Malmö that works as an inspiration for the development of future pocket parks and as a solution for the recovery, reclaiming of the public place, the right to the city, and the improvement of a better urban life.